Fusion using time-dependent density-constrained DFT - Keser, R.; Umar, A. S.; Oberacker, V. E.; Maruhn, J. A.; Reinhard, Paul-Gerhard (EPJ Web of Conferences, 2014)
We present results for calculating fusion cross-sections using a new microscopic approach based on a time-dependent density-constrained DFT calculations. The theory is implemented by using densities and other information obtained from TDDFT time-evolution of the nuclear system as a constraint on the density for DFT calculations. © Owned by the authors, published by EDP Sciences, 2014.
CRIS-Team Scopus Importer:2023-07-24